STUDI LITERATUR : ANALISIS MODEL BORG AND GALL DALAM PENGEMBANGAN DAN PENELITIAN PENDIDIKAN - Nabila Zuama Muthoharoh; Sri Marmoah (AT-TAKLIM: Jurnal Pendidikan Multidisiplin, 2025)
This study examines the Borg and Gall model as one of the most widely applied research and development (R&D) approaches in education. The main problem addressed is the limited understanding of the full implementation of its ten stages in Indonesia, as most studies simplify or modify them. The purpose of this research is to analyze the stages, strengths, weaknesses, and relevance of the Borg and Gall model in the context of 21st-century education and the Independent Curriculum. The method employed is a literature review, involving the analysis of theories, previous research, and expert perspectives. The findings indicate that the Borg and Gall model produces valid, innovative, and contextual educational products, yet requires significant time, cost, and resources. In conclusion, this model remains highly relevant as a methodological foundation to support adaptive, evidence-based, and needs-oriented learning innovation.